The Synergy of Religious and Political Policy Paradigms in the Preservation of Death Ceremonies in Muslim Communities - Purwanto, Bisri; Listiana, Anisa; Marpuah, Siti (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This article discusses the synergy of religious and government leaders in Muslim communities in preserving the tradition of death ceremonies in Menco Berahan Village, Demak Regency, Central Java Province.  The research method used is explorative descriptive qualitative. To find data collection using interviews and observations. While the data analysis techniques used in this study are data collection, data reduction, data display and verification. The results of this study indicate that the efforts of religious and government leaders in preserving the tradition of death ceremonies in Menco hamlet, Berahan Wetan Village are to provide support in the form of assistance and facilities.They agree that the death ceremony is one of the good deeds and is one of the obligations carried out by the family. The obligation to pray for the deceased family is realized by carrying out the death ceremony regardless of the economic condition of the family or community.   Therefore, the role of religious leaders and government leaders is responsible for finding solutions to the problems faced by the community in the hamlet so that the tradition of the death ceremony is still carried out. This research emphasizes the importance of synergizing the role of religious leaders with government leaders in policies to preserve religious traditions.